Organization and Provision of Buses Operation on the Route Taking Into Account the Expenditures of Participants of the Transportation Process - Ðœ. Ðœoroz, M; L. Khorolskyi, V; V. Ðœoroz, O; V. Vasylkovska, K; V. Herasymchuk, V (International Journal of Engineering and Technology, 2018)
The purpose of research. Determination of the optimal number of buses, taking into account the opposite economic factors and economic feasibility in new routes of passenger transport when changing the parameters of transport system using legislative methods and norms.Methods: The article defines the total expenditures of participants of passenger transportation process, which is influenced greatly by the number of buses on the route: on one hand, a large number of them provides the least amount of waiting time, on the other hand, with such quantity of buses carrierâ€™s expenditures increase, as well as the estimate and the cost account of the bus operation on the route using regulatory documents.Results: Using of the proposed methodology allows organizers and performers, in accordance with the current legislation, to overestimate (underestimate) costs deliberately (unintentionally), determine the economic expediency of opening new routes and calculating fares on existing routes and optimal number of buses on the route taking into account the influence of opposite factors. The compromise of the interests of the carrier and the passenger is influenced by the transport service time cost, operating costs and turnover time. Daily operating costs of the route studied and the volume of passenger traffic flow indicate that at the socially preferential (specified) by local council fare the carrier can cover expenditures by increasing the fare or targeted subsidies (subventions).Â Â Â